New contributions of measurements in Europe to the global inventory of the stable isotopic composition of methane - Menoud, Malika; van der Veen, Carina; Lowry, Dave; Fernandez, Julianne M.; Bakkaloglu, Semra; France, James L.; Fisher, Rebecca E.; Maazallahi, Hossein; Stanisavljević, Mila; Nęcki, Jarosław; Vinkovic, Katarina; Łakomiec, Patryk; et al. (Earth system science data, 2022)
Recent climate change mitigation strategies rely on the reduction of methane (CH4) emissions. Carbon and hydrogen isotope ratio (δ13C and δ2H) measurements can be used to distinguish sources and thus to understand the CH4 budget better. The CH4 emission estimates by models are sensitive to the isotopic signatures assigned to each source category, so it is important to provide representative estimates of the different CH4 source isotopic signatures worldwide. We present new measurements of isotope signatures of various, mainly anthropogenic, CH4 sources in Europe, which represent a substantial contribution to the global dataset of source isotopic measurements from the literature, especially for δ2H. They improve the definition of δ13C from waste sources, and demonstrate the use of δ2H for fossil fuel source attribution.
Gesehen am 08.11.2022